Outcome-based education curriculum implementation in arabic language education: A comparative study from a constructive alignment perspective - Agung Setiyawan; Haerul Ahyar; Fitri Zakiyah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2025)
Purpose – This study comparatively examines the implementation of an Outcome-Based Education (OBE) curriculum in Arabic Language Education programs at UIN Sunan Kalijaga Yogyakarta and Universitas Muhammadiyah Yogyakarta, focusing on constructive alignment among curriculum components and implementation dynamics across different institutional contexts. Method/design/approach – A qualitative multiple case study design was employed, with Arabic Language Education programs as the units of analysis. Data were collected through in-depth interviews, focus group discussions (FGDs), observations, and document analysis, and analyzed using thematic analysis with source and method triangulation. Findings – The findings indicate that both programs have adopted OBE principles in the formulation of program learning outcomes, course learning outcomes, course plans, and assessment practices. However, distinct implementation patterns were identified. UIN Sunan Kalijaga Yogyakarta applies an academic–reflective approach grounded in scholarly culture and lecturer collaboration, whereas Universitas Muhammadiyah Yogyakarta adopts a systemic–digital approach supported by the SIM-OBE system for monitoring learning outcomes. Digital systems enhance traceability and evaluation of learning outcomes, although consistent constructive alignment across outcomes, learning strategies, and assessment remains a challenge in both institutions. Lecturer workload and administrative complexity emerged as key constraints affecting classroom-level implementation. Implikasi/batasan penelitian – This study contributes theoretically by offering a comparative perspective on OBE implementation in Islamic higher education, emphasizing the integration of academic–reflective and systemic–digital approaches. Practically, the findings inform program managers in developing sustainable strategies for strengthening OBE implementation. The study is limited to two institutional cases, which may restrict broader generalization Originality/value - By integrating constructive alignment with institutional context analysis, the study enriches the discourse on outcome-based curriculum development in Islamic higher education.